2019
DOI: 10.20473/bhsj.v2i1.11549
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Urinary Tract Infection in Hospitalized Patients

Abstract: Introduction: Urinary tract infection (UTI) is the most common infection that can be fatal and has higher rate mortality especially in some patient. This study is aim to analyze risk factors for urinary tract infection in hospitalized patients for prevention and more aggressive approach can be taken.Methods: Consecutively, medical records of 285 patients with urinary analysis was recorded for risk factors and urine culture results if suspected UTI. Risk factors for sex, age, urinary catheter, urolithiasis, DM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…This result was supported by other previous studies in Indonesia and other countries as well (Ren et al 2016, Pratistha et al 2018, Setyorini et al 2019. Fimbriae, flagella, toxins, pili, curli, and iron acquisition systems are some virulence factors that help E. coli cause infection (Terlizzi et al 2017).…”
Section: Microbiological Investigationsupporting
confidence: 82%
See 1 more Smart Citation
“…This result was supported by other previous studies in Indonesia and other countries as well (Ren et al 2016, Pratistha et al 2018, Setyorini et al 2019. Fimbriae, flagella, toxins, pili, curli, and iron acquisition systems are some virulence factors that help E. coli cause infection (Terlizzi et al 2017).…”
Section: Microbiological Investigationsupporting
confidence: 82%
“…Nearly 74% of the E. coli strain in this study was an ESBL-producing strain. Another study in the same area that used data in the year 2018 mentioned that only 34.78% of the E. coli strain produces ESBL in hospitalized patients (Setyorini et al 2019). The data indicated that there was a rapid spreading of the ESBL gene in the clinical environment as Indonesia is a country where there is the emersion and transmission of ESBL genes harbored inside the bacterial strains (Severin et al 2010).…”
Section: Microbiological Investigationmentioning
confidence: 99%
“…This is consistent with an earlier study by Hariati et al (2019) who found that CAUTI was more prevalent in people over 60 years old. Older age and immobility were two additional significant risk variables, although they could be influenced by other factors (Setyorini et al 2019). Patients with diabetes mellitus have a significant risk of developing urinary tract infections since their urine is a source of microbial growth, and they typically have immunocompromised states.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Santosaningsih et al (2018) dalam penelitiannya menemukan bahwa 257 dari 567 (45,3%) pasien rawat jalan pada 10 fasilitas kesehatan di Pulau Jawa dan Bali mengalami infeksi kulit dan jaringan lunak karena Staphylococcus aureus. Sedangkan, pada penelitian yang dilakukan oleh Setyorini et al (2019) menyatakan bahwa Escherichia coli menjadi patogen yang paling banyak menyebabkan infeksi saluran kemih dibandingkan 25 spesies bakteri lain yang diuji pada pasien rawat inap di RSUD dr. Soetomo, Surabaya, yaitu sebanyak 41,3%, oleh karena itu, Escherichia coli dan Staphylococcus aureus menjadi bakteri yang sering menyebabkan infeksi terkait pelayanan kesehatan sehingga dibutuhkan media pertumbuhan bakteri yang memadai pada laboratorium di pelayanan kesehatan untuk menegakkan diagnosis infeksi akibat kedua bakteri tersebut. Berdasarkan uraian fenomena di atas, maka perlu untuk melakukan penelitian dengan menjadikan limbah ikan bandeng (Chanos chanos) sebagai media altenatif Agar Nutrien dan menganalisis kemampuannya pada pertumbuhan Escherichia coli dan Staphylococcus aureus.…”
Section: Pendahuluanunclassified